Investigation of Security Aspect of Cloud Computing - Klim, Sahar Mahdie (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Cloud Computing is an evolving computing pattern in which resources of the computing infrastructure are provided as services over the Internet. This pattern also fetches forth many new challenges for data security and access control when users outsource sensitive data for sharing on cloud servers, which are not within the same trusted domain as data owners. To keep sensitive user data confidential against untrusted servers, existing solutions usually apply more security modes. In this study, we focused on the security aspect of the cloud computing. We proposed a unique extremely of decentralization information accountability context to remain follow from particular usage of the clients’ information within the cloud; it aims to ensure more secure usage of data by providing supplementary security mode in the application of system. So we concentrated on three security modes: Accountability, Auditing Mechanism and Automatic Session Expire Technic for the web application. In our application there are three parties, namely: Admin, Owner and User. We reinforce data security over cloud through the mentioned security modes. In our system only legally registered clients are eligible to access to stored data. Moreover, an advanced auditing mechanism is implemented, in which the owner can monitor the data while the admin can observe and control all the system. Furthermore, we included expiry session feature to improve the application security. Above all, this study is suggesting a degree of object-related approach which allows inclusion of our registration and logging procedure together with users’ information and policy. We also leveraged the Java Archive Rar (JAR) programmable capabilities to both create a dynamic and traveling object, and to ensure that any access to users’ data will trigger authentication and automated logging local to the JARs. And as mentioned above to strengthen user’s control, we provided distributed auditing mechanisms. Finally we provided extensive experimental studies that demonstrate the efficiency and effectiveness of the proposed approaches. Keywords: Cloud computing, security, accountability, Java Archive Rar (JAR)

ÖZ; Bulut bilişim (cloud computing) alt yapı kaynakları Internet üzerinden sağlayan ve gelişmekte olan bir bilişim modelidir. Bu modelde kullanıcılar ve veri sahipleri aynı güvenli alan içerisinde olmayabildiklerinden, kullanıcılar hassas verilerini bu sistem üzerinde paylaşırken veri güvenliği ve erişim kontrolü ile ilgili farklı sorunlar yaşamaktadırlar. Hassas verileri güvenilir olmayan sunucularda korumak için mevcut çözümler daha güvenilir bir şekilde uygulanmaktadır. Bu çalışmada, bulut bilişim sistemlerinin güvenlik yönleri üzerinde durulmuştur. Önerilen ek güvenlik yöntemleriyle kullanıcıların verilerinin sistemde daha güvenli bir şekilde tutulması ve kullanımlarının sağlanması hedeflenmiştir. Bu amaç için sistem yöneticisi, veri sahibi ve kullanıcılar için üç farklı güvenlik yöntemi üzerinde durulmuştur. Sisteme kayıt yaptırarak girebilme, sisteme girişlerin denetlenmesi ve sistemde tutulan verilere kullanım süresinin verilmesi yöntemleriyle bulut bilişim sistemlerinin güvenliği artırılmaya çalışılmıştır. Oluşturulan sistemde, sadece yasal olarak kayıt yaptıran kullanıcıların verilere giriş izni vardır. Aynı zamanda, oluşturulan denetim mekanizması ile, veri sahibi girişleri gözlemleyebilirken, sistem yöneticisi de tüm sistemi gözlemleyip kontrol edebilmektedir. Bunlara ek olarak, sistemde saklanan dosyalara geçerlilik süresi verilerek dosyaların sistemde saklanma süreleri kısıtlanmış ve verilerin güvenliği artırılmıştır. Bütün bunların yanında, bu çalışmada kullanıcı kaydı ve girişi işlemleri için nesneye dayalı yöntemler kullanılmaktadır. Aynı zamanda, Java Arşiv Rar (JAR) programlama yöntemleri kullanılarak dinamik ve taşınabilir nesneler yarıtılmış kullanıcı verilerine kimlikle erişim sağlamış ve kullanıcıların girişleri kontrol altına alınmıştır. Çalışmanın sonunda oluşturulan sistem üzerinde bazı deneyler yapılarak sistemin etkinliği, önerilen yöntemlerin etkisi gözlenmiştir. Anahtar kelimeler: Bulut bilişim, güvenlik, denetimlilik, Java Arşiv Rar (JAR)
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2014. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Cloud computing - Security measures - Data protection; Cloud computing; security; accountability; Java Archive Rar (JAR)